Maternal Lineage Structure and Chloroplast Diversity of South Sumatran Rice, Indonesia, Revealed by the trnH–psbA Intergenic Spacer - Fikri Adriansyah Adriansyah; Rujito Agus Suwignyo; Andi Wijaya; Upit Sarimana; Imam Wibisono; Nabilah Amiros (Universitas Panji Sakti, 2026)
Despite the importance of comprehensive genetic characterization for the conservation and utilization of local rice germplasm in breeding programs, the maternal genetic diversity of South Sumatran local rice remains largely unexplored. In this study, we evaluated the genetic diversity, maternal lineage, and phylogenetic relationships of South Sumatran rice accessions using the chloroplast trnH–psbA intergenic spacer, a highly variable chloroplast marker widely used for assessing genetic diversity and phylogenetic relationships in rice and other plant species. A total of 18 South Sumatran rice accessions, along with reference sequences, were analyzed through sequence alignment, haplotype network construction, genetic distance clustering, and phylogenetic tree reconstruction using the Neighbor-Joining (NJ) and UPGMA methods. The trnH–psbA region showed a uniform sequence length of 415 bp and low nucleotide diversity (π = 0.096%), resulting in the identification of three haplotypes. Phylogenetic and genetic distance analyses consistently identified two accessions, Bone 1 and Pegagan 2, as genetically distinct, highlighting their potential value as candidates for future conservation and breeding initiatives. These findings provide a molecular basis for the preservation and strategic utilization of South Sumatran rice germplasm and emphasize the importance of conserving genetically divergent local accessions. Future studies integrating chloroplast and nuclear markers will enable a more comprehensive assessment of genetic diversity for rice breeding and conservation.